Electronic Health Record Workstation Single Sign-on: A Quantification of Time Liberated for Nurses to Care for Patients. (September 2020) - Gellert, George A.; Ramirez, Ricardo; Jacobs, Walter J.; Maciaz, Gabriel
Abstract : OBJECTIVE: The aim of this study was to quantify the impact of electronic health record (EHR) workstation single sign-on (SSO) for nurses. BACKGROUND: SSO was implemented in 19 hospitals for expedited EHR access. METHODS: Login durations before and after SSO implementation were compared, and the financial value of nursing time liberated from keyboard was estimated. Stratified analyses show time liberated and financial value by staffing level and system size. RESULTS: First-of-shift login was reduced by 5.3 seconds (15.3%) and reconnect duration was reduced by 20.4 seconds (69.9%). SSO liberated 27, 962.4 hours of nursing time from keyboard login per year across 19 facilities, and 1, 471.7 hours/year/facility, valued at $52, 112/facility and $990, 128 for 19 hospitals. Time value ranges from $201, 835 per year for a 5-hospital system with 300 nurses per facility to $672, 790 per year for a 10-facility system with 500 nurses per hospital. CONCLUSIONS: Nurses gained substantial time liberated from EHR keyboard by SSO for patient care, having significant financial value for the organization.